Topic maps constraint languages : understanding and comparing - Librelotto, Giovani Rubert (2009)
Topic map constraint language (TMCL) provides a means to express constraints on topic maps conforming to ISO/IEC 13250. In this article, we will use a test suite and show, step-by-step, the way we handled several kinds of topic maps constraints in many different instances in order to answer questions like: Do they do the same job? Are there some kinds of topic maps constraints that are easier to specify with one of them? Do you need different background to use the tools? Is it possible to use them in similar situations (the same topic maps instances)? May we use them to produce an equal result? How do AsTMa!, OSL, Toma and XTche relate to TMCL? What kind of constraints each one of these three cannot specify? We will conclude this paper with a summary of the comparisons accomplished between those topic maps constraint languages over the use case proposed.